Unleashing the potential: transforming technical and vocational education and training - Marope, Priscilla Toka Mmantsetsa; Chakroun, Borhène; Holmes, K. P (2015)
"UNESCO has recently published the third volume of its Education on the Move series, a series dedicated to the analysis of key trends in education with the hope of inspiring dialogue among policy makers, educators and other key stakeholders on the challenges of education for tomorrow. The latest publication, entitled Unleashing the Potential: Transforming Technical and Vocational Education and Training is focused entirely on issues related to technical and vocational education and training (TVET). It takes stock of the steadily increasing demands and expectations on TVET systems around the globe and presents recent policy trends in the field of TVET. In their analysis, the authors provide insights into what it takes to unleash the potential of TVET systems around the world. They propose an integrated analytical approach that takes into consideration such factors as economic growth, social equity and issues related to sustainability so that TVET can contribute more effectively to contemporary policy issues such as youth unemployment, gender disparities and climate change. Overall, the book calls for a transformation of TVET systems to enable them to respond to the demands of their contexts. This transformation should enable TVET systems to acquire agility to stay current and responsive to the rapidly changing demands of the twenty-first century."–Publisher's website.
OCLC: 921829960 KerkoCite.ItemAlsoKnownAs: 2129771:AVKWPPMP 2317526:JK6589HH